Neoechinorhynchus pterodoridis n. sp. (Acanthocephala: Neoechinorhynchidae) do bacu liso (Pterodoras granulosus) da Amazônia Brasileira - Thatcher, Vernon Everet (Acta Amazonica, 1981)
Neoechinorhynchus pterodoridis n. sp. (Acanthocephala: Neoechinorhynchidae) is described from the intestine of a freshwater fish called the "bacu liso" (Pterodoras granulosus (Velenciennes) taken in the Amazon River near Manaus. Amazonas, Brazil. The new species is among the smallest known in the genus being comparable in size and form to N. paraguayensis Machado, 1954, and to N. golvani Salgado-Maldonado, 1979. The new species is readily distinguished from these two species by the presence of a conspicuous neck region and by differences in the hook measurements.